2022
DOI: 10.1021/acs.jpcc.2c05895
|View full text |Cite
|
Sign up to set email alerts
|

Charge Redistribution in Mg-Doped p-Type MoS2/GaN Photodetectors

Abstract: MoS2/GaN p–n heterojunction photodetectors with enhanced built-in electric field have paved the way for nanoelectronic and nano-optoelectronic applications. However, the realization of p-type MoS2/n-type GaN p–n heterostructures is still challenging because of the complex and unstable preparation process of p-type MoS2. Herein, Mg-doped p-type MoS2/GaN p–n heterojunctions have been synthesized via a two-step method involving electron beam evaporation and chemical vapor deposition. First-principles calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In this case, electron energy loss spectroscopy (EELS) at the single-atom level can help identify the element and its local atomic configurations [82,83]. Studies showed that some elements tend to form clusters, among them Co [82], Te [84], Re with a concentration below 1 at% [85,86], Se [87], W [88,89], Mn [90], Mg [91], Sb [92], and Ru [93] are distributed randomly regardless of concentration. Figure 5a shows an example of the identification of two different Co defects in a MoS 2 monolayer by the HAADF/STEM method.…”
Section: Experimental Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, electron energy loss spectroscopy (EELS) at the single-atom level can help identify the element and its local atomic configurations [82,83]. Studies showed that some elements tend to form clusters, among them Co [82], Te [84], Re with a concentration below 1 at% [85,86], Se [87], W [88,89], Mn [90], Mg [91], Sb [92], and Ru [93] are distributed randomly regardless of concentration. Figure 5a shows an example of the identification of two different Co defects in a MoS 2 monolayer by the HAADF/STEM method.…”
Section: Experimental Detectionmentioning
confidence: 99%
“…Doping causes a shift of the Fermi level of the compound, resulting in a change in the binding energy of the core-level electrons as compared to the undoped compound [96]. For example, a decrease in the binding energy of the Mo 3d 5/2 and S 2p 3/2 components was observed for MoS 2 doped with Mg [91], Ru [93], N [97], and Nb [98,99], while the introduction of Re [86] or Se [87] substituents resulted in an increase in the binding energies.…”
Section: Experimental Detectionmentioning
confidence: 99%
“…), or polymer matrix. [ 19–27 ] Wherein, SiO 2 coating process is relatively mature and has been widely used for surface modification of nanoparticles (NPs) to improve stability and biocompatibility, as well as to reduce the toxicity. Surface coating silica has been proved to be an effective strategy to improve the stability of CsPbBr 3 NCs in water.…”
Section: Introductionmentioning
confidence: 99%
“…9 Doping technology is one of the effective means of modulating the optical and electrical properties of semiconductors. Several doping strategies, including charge transfer doping, 10 electrostatic doping, 11 and element doping, 12 have been proposed for MoS 2 to improve its NIR photoresponse. Element doping, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…9 Doping technology is one of the effective means of modulating the optical and electrical properties of semiconductors. Several doping strategies, including charge transfer doping, 10 electrostatic doping, 11 and element doping, 12 have been proposed for MoS 2 to improve its NIR photoresponse. Element doping, i.e., introducing a dopant into the host, results from the added impurity energy levels 13 and trap states 14 or the altered electron transport characteristics.…”
Section: Introductionmentioning
confidence: 99%